Reduced hippocampal and amygdala volume as a mechanism underlying stress sensitization to depression following childhood trauma. Issue 9 (24th June 2020) - Weissman, David G.; Lambert, Hilary K.; Rodman, Alexandra M.; Peverill, Matthew; Sheridan, Margaret A.; McLaughlin, Katie A.
Abstract: Background: Stressful life events are more likely to trigger depression among individuals exposed to childhood adversity. However, the mechanisms underlying this stress sensitization remain largely unknown. Any such mechanism must be altered by childhood adversity and interact with recent stressful life events, magnifying their association with depression. Aim: This study investigated whether reduced hippocampal and amygdala volume are potential mechanisms underlying stress sensitization following childhood violence exposure. Method: A sample of 149 youth (aged 8–17 years), with ( N = 75) and without ( N = 74) exposure to physical abuse, sexual abuse, or domestic violence participated. Participants completed a structural MRI scan and assessments of depression. Approximately 2 years later, stressful life events were assessed along with depression symptoms in 120 participants (57 violence exposed). Results: Childhood violence exposure was associated with smaller hippocampal and amygdala volume. Stressful life events occurring during the follow‐up period predicted worsening depression over time, and this association was magnified among those with smaller hippocampal and amygdala volumes. Significant moderated mediation models revealed the indirect effects of violence exposure on increasing depression over time through hippocampal and amygdala volumes, particularly among youths who experienced more stressful life events. Conclusions: These results provide evidence for reduced hippocampal and amygdala volume as potential mechanisms of stress sensitization to depression following exposure to violence. More broadly, these patterns suggest that hippocampal and amygdala‐mediated emotional and cognitive processes may confer vulnerability to stressful life events among children who have experienced violence.